An Experimental Investigation of Alternatives to Expected Utility Using Pricing Data - Andrea Morone; Ulrich Schmidt (Kiel University, Department of Economics, 2006)
Experimental research on decision making under risk has until now always employed choice data in order to evaluate the empirical performance of expected utility and the alternative nonexpected utility theories. The present paper performs a similar analysis which relies on pricing data instead of choice data. Since pricing data lead in many cases to a different ordering of lotteries than choices (e.g. the preference reversal phenomenon) our analysis may have fundamental different results than preceding investigations. We elicit three different types of pricing data: willingness-to-pay, willingness-to-accept and certainty equivalents under the Becker-DeGroot-Marschak (BDM) incentive mechanism. One of our main result shows that the comparative performance of the single theories differs significantly under these three types of pricing data.
Keywords: D81; C91; 330; expected utility; non-expected utility; experiments; WTP; WTA; BDM; Erwartungsnutzen; Entscheidung bei Risiko; Experiment; Willingness to pay; Verhaltensökonomik; Theorie